Education and Training in Pediatric Cardiac Critical Care: International Perspectives. Issue 6 (November 2019) - Zyblewski, Sinai C.; Callow, Louise; Beke, Dorothy M.; Jain, Parag; Madathil, Sai Bala; Schwartz, Steven; Tabbutt, Sarah; Bronicki, Ronald A.
Pediatric cardiac intensive care is an evolving and maturing field. There have been advances in education and training in recent years, specifically progress toward standardization of curricula, competencies, and certifications. International partnerships have fostered similar advancements in less resourced countries. For all disciplines and levels of expertise, simulation remains a versatile and effective modality in education. Although there is improved standardization for the training of physicians and nurses, the certification process remains undetermined.